(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The current political system varies depending on the country and region. However, there are some common trends and characteristics that can be observed. In many countries, there is a trend towards populism, nationalism, and authoritarianism. This has led to the rise of leaders who are seen as strongmen, who prioritize national interests over global cooperation, and who often use divisive rhetoric to appeal to their base. There is also a growing concern about the erosion of democratic norms and institutions, particularly in countries where there are restrictions on freedom of speech, press, and assembly. This has led to challenges to the rule of law, and concerns about the independence of the judiciary and the media. At the same time, there are also movements towards greater social justice and equality, particularly around issues such as racial justice, gender equality, and climate change. These movements have challenged traditional power structures and called for greater accountability and transparency in government.